2011
DOI: 10.1029/2011gc003617
|View full text |Cite
|
Sign up to set email alerts
|

Domains of depleted mantle: New evidence from hafnium and neodymium isotopes

Abstract: [1] Isotope systematics of basalts provide information on the distribution of mantle components and the length scale of mantle heterogeneity. To obtain this information, high data and sampling density are crucial. We present hafnium and neodymium isotope data on more than 400 oceanic volcanics. Over length scales of several hundred to over one thousand kilometers hafnium and neodymium isotopes of mid-ocean ridge basalts are correlated and form an array of parallel trends on a global scale. On a larger scale th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 128 publications
(209 reference statements)
12
122
1
1
Order By: Relevance
“…Etna through time. Lassiter et al, 2003;Stracke et al, 2003;Gaffney et al, 2004;Huang et al, 2005;Xu et al, 2007;Sims et al, 2008;Blichert-Toft and Albarède, 2009;Yamasaki et al, 2009;Garcia et al, 2010;Peate et al, 2010;Chekol et al, 2011;Salters et al, 2011;Viccaro et al, 2011); mantle components from Zindler and Hart, 1986;Salters and White, 1998;Workman et al, 2004;Stracke et al, 2005;Workman and Hart, 2005. Hafnium isotopic values for Italian sediments (Conticelli et al, 2002;Brems et al, 2013) are calculated from Nd isotopic data and both cases following the seawater array (SA) and the terrestrial array (TA) of Vervoort et al (2011) Trua et al (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Etna through time. Lassiter et al, 2003;Stracke et al, 2003;Gaffney et al, 2004;Huang et al, 2005;Xu et al, 2007;Sims et al, 2008;Blichert-Toft and Albarède, 2009;Yamasaki et al, 2009;Garcia et al, 2010;Peate et al, 2010;Chekol et al, 2011;Salters et al, 2011;Viccaro et al, 2011); mantle components from Zindler and Hart, 1986;Salters and White, 1998;Workman et al, 2004;Stracke et al, 2005;Workman and Hart, 2005. Hafnium isotopic values for Italian sediments (Conticelli et al, 2002;Brems et al, 2013) are calculated from Nd isotopic data and both cases following the seawater array (SA) and the terrestrial array (TA) of Vervoort et al (2011) Trua et al (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Anomalously high values of 177 Hf/ 176 Hf for a given 143 Nd/ their mantle source across the garnet-spinel transition beneath the mid-oceanic ridge (Blichert-Toft et al, 2005;Debaille et al, 2006). More recently, a systematic study of Hf-Nd isotopes in oceanic basalts has shown an array of parallel trends on a global scale (Salters et al, 2011). These authors attributed these sub-parallel arrays to the involvement of varying amounts of highly residual peridotites within the upper mantle.…”
Section: Introductionmentioning
confidence: 96%
“…Further, some refractory portions of the DMM may not be accessed at all in the production of MORB. Evidence for considerable heterogeneity in the DMM, beyond the range sampled by MORB, includes the fact that some peridotites that directly sample the DMM have much more radiogenic 143 Nd/ 144 Nd and 176 Hf/ 177 Hf than any known MORB (e.g., Sharma et al, 1995;Warren et al, 2009a;Salters et al, 2011;Stracke et al, 2011). Thus, the nature and scale of chemical heterogeneity in the modern DMM may be utilised to reveal important secrets of the mantle.…”
Section: Overview Of the Dmmmentioning
confidence: 99%
“…Such research has been fruitful because of the extent to which MORBs have been sampled throughout all of the ocean basins (e.g., Klein and Langmuir, 1987;Workman and Hart, 2005;Salters et al, 2011). Thus, MORB research has elucidated global variations in the chemical and isotopic nature of the DMM.…”
Section: Overview Of the Dmmmentioning
confidence: 99%
See 1 more Smart Citation